The analysis of air-cooled heat exchanger for Reactor Cavity Cooling System (RCCS) on Experimental Power Reactor (RDE) design. (March 2020) - Susmikanti, Mike; Yunus, Muhammad; Tjahjono, Hendro; Kusumastuti, Rahayu; Sulistyo, Jos Budi
Abstract: The National Nuclear Energy Agency (BATAN) is designing the Experimental Power Reactor (RDE). The Reactor Cavity Cooling System (RCCS) is a new basic design in the nuclear power plant. It will be incorporated into High-Temperature Reactors (HTR), which is one proposed generation of IV reactors. While HTR has been designed and operated, the RCCS design is unique to the recent generation of gas-cooled reactors as a passive decay heat removal system. However, many aspects of the new air- or water-cooled design still need to be investigated on RCCS. The temperature, mass flow, configuration of the riser, and number of the risers on the water-cooled heat exchanger system which is used is a necessary test. The RCCS designs have not been studied for the RDE design. The heat-transfer and fluid-flow on the RCCS facility have not been investigated for the air-cooled cavity cooling system. The aim of this study is to examine the condition of the air-cooled heat exchanger of RCCS for RDE 10 MWth design. The pressure, temperature, and velocity with certain diameters of cooling pipes are computed with FLUENT 6.3 computational fluid dynamics (CFD) software package under a mass flow rate variation. The pressure, the flow velocity and delta temperature outlet were examined on the RCCS process. The air-cooled heat exchanger in RDE basic design was found to attain safe operation.